BODY IMAGE AND SELF ESTEEM AMONG COLLEGE GOING GIRLS - Kaur, Ms. Amritpal (The journal of contemporary issues in business and government, 2019)
The present study was carried out to examine the role of body image as a predictor of self esteem among college going girls. For this purpose, the data were collected from 127 girls studying in the government colleges affiliated with University of Jammu. Pearson product moment of correlation and simple linear regression was used for statistical analyses of the data. Significant and positive relationship came out between perception of body image and self esteem. Overall model summary and regression coefficients revealed body shape is a significant predictor of self esteem in college going girls. The model came out to be significant at 0.01 level. The result of the study indicates that perception of body image is one of the important factors related to self esteem among college going girls.